Combined morphological and molecular approaches reveal Conocybe pakistanensis (Bolbitiaceae), a novel species from Punjab, Pakistan - Akram, Wajahat; Saba, Malka; Asif, Muhammad; Maula, Fazli; Batool, Momal; Kamal, Asif; Noor, Atika (Phytotaxa, 2025)
This study significantly contributes to fungal taxonomy by integrating morphological and phylogenetic analyses using ITS and 28S sequences. Focusing on the Conocybe genus in Pakistan, the combined strategy has effectively identified a new species i.e. C. pakistanensis. The new species is distinguished by a broadly parabolic pileus, with dull orange lamellae, ellipsoid to oblong basidiospores with prominent germ pores, bisporic basidia, lecythiform cheilocystidia, and caulocystidia but vary in size of neck and capitulum, and epithelioid hymeniderm pileus composed of globose to subglobose elements. This research advances our understanding of fungal diversity by investigating morphological characteristics and genetic profiles. The morphological, ITS and combined ITS-28S based phylogenetic studies revealed that the new species nested within C. sect. Conocybe. This finding not only broadens our understanding of local fungal biodiversity but also demonstrates the value of a comprehensive methodology.